Oxidative Coupling Copolymerization of 2, 6-Dimethylphenol and Dihydroxynaphthalene Affording Poly(phenylene oxide) Derivatives. (16th July 2015) - Habaue, Shigeki; Ito, Ryosuke; Okumura, Ken; Takamushi, Yuki
Abstract : The oxidative coupling copolymerization between 2, 6-dimethylphenol (DMP) and dihydroxynaphthalenes, such as the 2, 3- and 2, 6-dihydroxynaphthalenes (2, 3- and 2, 6-DHN), was carried out using a Cu catalyst under an O2 atmosphere. The polymerization was significantly affected by the structure of the comonomer, and the copolymers were efficiently obtained during the copolymerization of DMP and 2, 6-DHN. The obtained copolymers containing hydroxyl groups of the DHN unit were further transformed into polymers containing ester and urethane groups. The obtained copolymers containing various functional groups showed a very different solubility from that of the homopolymer of DMP.